Scale‐dependent patterns of metacommunity structuring in aquatic organisms across floodplain systems. (19th December 2020) - Lansac‐Tôha, Fernando M.; Bini, Luis M.; Heino, Jani; Meira, Bianca R.; Segovia, Bianca T.; Pavanelli, Carla S.; Bonecker, Claudia C.; de Deus, Claudia P.; Benedito, Evanilde; Alves, Geziele M.; Manetta, Gislaine I.; Dias, Juliana D.; et al.
Abstract: Aim: Evaluating how groups of organisms vary in dispersal capability and how environmental, spatial and temporal signals vary across multiple scales is critical to elucidating metacommunity theory. We examined whether the relative contributions of environmental, spatial and hydrological factors have different effects on organismal groups with different dispersal abilities at three spatial scales, and how this knowledge contributes to our understanding of metacommunity dynamics. Location: Four major Brazilian floodplains, with the largest distance among them of 2, 300 Km. Taxon: 10 aquatic organismal groups, ranging from bacterioplankton to fish. Methods: We sampled lakes connected to the main river in the low‐ and high‐water periods of each floodplain between 2011 and 2012. Different biological groups were analysed across three hierarchical spatial scales (fine, intermediate and subcontinental) within and between floodplain systems. We applied a series of partial redundancy analyses to estimate the relative contributions of environmental factors, spatial factors and hydrological period for each biological group. Results: At the fine spatial scale, predominantly environmental factors and hydrological period structure metacommunities, although less so for microorganisms than for micro‐invertebrates and macro‐organisms. The relative importance of environmental factors increased at the intermediate spatial scale. At the subcontinental scale, the relative importance of spatial factors increased for all biological groups, but environmental factors remained the primary regulators of microorganisms even at the largest scale. Main conclusions: This study design allowed us to make more robust inferences about the mechanisms responsible for regulating community structure of distinct biological groups at different spatial scales. Our results suggest that biological groups displaying distinct body size likely determine the spatial extent at which environmental, spatial and hydrological processes prevail as the primary regulators of community structure. These findings are important in guiding the conservation and management of floodplain biodiversity because these systems are naturally highly heterogeneous in space and time.